Penggunaan Gamifikasi Berbasis Quizizz untuk Meningkatkan Kepuasan Siswa dalam Pembelajaran Geografi - Anggun Sasmita; Paus Iskarni; Dedi Hermon (Jurnal Penelitian Pendidikan IPA, 2025)
The rapid advancement of digital technology has transformed educational practices, particularly through the integration of gamified learning platforms such as Quizizz. This study aimed to explore students satisfaction with the use of Quizizz in Geography learning and to identify which aspects most influence their learning experience. Employing a descriptive quantitative design, data were collected from 35 tenth grade students through a Likert-scale questionnaire measuring four key indicators: interactivity, ease of use, learning motivation, and material comprehension. Data were analyzed using mean scores and frequency distribution to determine overall satisfaction levels. The results revealed that students satisfaction with Quizizz based gamification was categorized as neutral (mean=3.01). Among the four aspects, material comprehension obtained the highest score (mean=3.13), suggesting that real-time feedback effectively supported students conceptual understanding. In contrast, learning motivation recorded the lowest score (mean=2.90), indicating possible fatigue from repetitive quiz formats and competitive features. Technical barriers, such as unstable internet connections, also affected students engagement and comfort. These findings suggest that while Quizizz provides valuable interactive learning experiences, its effectiveness depends on pedagogical variation and contextual adaptation. Teachers are encouraged to integrate gamified tools strategically to sustain motivation and enhance overall student satisfaction in Geography education